Study of Tobacco Smoke and Pregnancy Outcome (Medico Legal Update, 2020)
Introduction. Pregnant women have a risk for tobacco smoke both actively and passively. Pregnant womenare usually exposed to enviromental tobacco smoke (ETS) in various places with different duration of time.Cigarette smoke has a severe effect not only on pregnant women but also on the fetus.Methods Variousreferences were collected from online database including reports, journals, mostly in the last 10 years. Thejournals were mostly from the scholarly journals.Results. Tobacco smoke can effect the immunity, hormonal and metabolic system of the pregnant woman,therefore disturbing the growth of the fetus. Tobacco smoke also known to increase the risk of prematurebirth and reduce gestational age. Tobacco smoke cause several problems in newborn such as respirationdistress, low birth weight (LBW), neural disorder, sudden infant death syndrome (SIDS) and congenitalanomaly.Conclusion. The effect of tobacco smoke, actively of passively, have worse outcome for the pregnantwomen and their babies.